Perancangan Interior Bistro dan Booth “Leker Boss” di Surabaya - Meliana Meliana (Intra, 2017)
Leker Bos is one of the newly developed food business which sell Leker in a modern way. Currently, the business is having a difficulty in capturing people interest to buy its product. The reason behind this, is because there are many competitors whom also sell the same product, however appear to have a better appealing booth and consistency value. Through this fact, Interior Design Planning is needed to enhance the Leker Boss Brand. Bistro Interior Model in a permanent spot, semi-permanent booth model, and efficient Leker Boss mobile booth for a mobile commercial activity are the type of planning needed. According to the planning, the design thinking method will be applied. It encompasses three main stages, inspiration (understand, observe, pov), ideation (ideate, prototype, test), and implementation (story-telling, pilot, business model). The result from applying the design and also thinking method is producing the smallest effective module that enhances the mobility of the booth in any spot given. This module provides Leker Boss business three alternative booth which are Bistro Interior Model in a permanent spot, semi-permanent booth model, and efficient Leker Boss mobile booth for a mobile commercial activity.